Security and Privacy Applications for Smart City Development. - (:unkn) unknown (Springer, 2021)
This book explores the fundamentals of smart cities along with issues, controversies, problems and applications concerning security and privacy in smart city development. Future smart cities must incorporate innovations like smart rainwater harvesting, smart street lighting, digital identity management, solar energy, intelligent transport systems and emerging communication applications. The target audience of the book includes professionals, researchers, academics, advanced-level students, technology developers, doctors and biologists working in the field of smart city applications. Professionals will find innovative ideas for marketing and research, while developers can use various technologies like IoT and block chain to develop the applications discussed here. As the book shows, by integrating new technologies, the cities of the future are becoming a reality today.
Keywords: Smart City; Stadtmanagement; Cyberspace; Öffentliche Sicherheit; Sicherheitskonzept; Identifizierung; Digitaltechnik; Kommunikationstechnologie; Anwendungsbereich; Planungsinstrument; Steuerung; Regenwasserbewirtschaftung; City-Logistik; Stadtbeleuchtung; Datenschutz; Privater Raum; Big Data; Internet der Dinge